Translation and Alterity: A Study of In this Life, by Michael O’Loughlin - Alencar, Julia Gomes de (ABEI Journal, 2017)
The current research analyses the relationship between the poetsMichael O’Loughlin and Mikelis Norgelis, two individual writers, who are,however, the same person. Norgelis, a Latvian immigrant, is O’Loughlinhimself, an Irish poet who, upon his return to Ireland after years abroad, finds a new voice to his writings. The discussion is based on the book In This Life, 2011 in which there are twelve poems under O’Loughlin’s authorship, and eight under Mikelis’. This structure ends up raising the question “Who, then, is Norgelis?” Is he a heteronym, a mask of O’Loughlin, or a translation of himself? Both Venuti (2008) and Tejaswini Niranjana (1992) claim that translation can be a political instrument – an instrument expertly used by O’Loughlin when reinventing himself. As Norgelis, he was allowed to play with the English language in ways that, as an Irishman, he could not do. It was through this new identity and culture that he was able to write again in the Ireland he was coming to know once more. The search for his identity made necessary thechange of his political being, making him adapt in an emigrant and immigrants country. As a translator of himself, O’Loughlin’s transformation is not a faithful one: he becomes the colonized, with the power of choosing which reality to represent. O’Loughlin becomes the author and the translator in his book In This Life, blurring even more the lines between the marks of the translator and the illusion of his invisibility.